Augmented reality battleship board game with holographic display. Issue 1 (November 2020) - Fadzli, F E; Ismail, A W; Rosman, M F A; Suaib, N M; Rahim, M S M; Ismail, I
Abstract: The board game is a game that played on the board, and the Battleship board game is one of the examples. While developing the virtual board game, multi-user interaction is essential as a board game played by more than one people. To enhance the user experience, the board game has been implemented with Augmented Reality (AR) technology. AR can superimpose it into the real-world since it has the capabilities to overlay the virtual game on the top of the real world. However, AR handheld has limited perspective viewing for the viewers to see the battleship game. Therefore, this project aims to develop an AR battleship board game with a holographic display. Three phases have been carried out, first is to study the multi-user interaction for the AR battleship board game and holographic display with a different perspective. Second is to develop the multi-user interaction for AR Battleship board game. Finally, the third phase is to integrate the AR Battleship board game with a pyramid holographic display. The evaluation has been performed, and the result is based on the usability and user acceptance have been recorded. Based on the result, this project has successfully produced AR Battleship board game with holographic display application and significantly enhance the user experience.